2010
DOI: 10.1142/s0217751x10047956
|View full text |Cite
|
Sign up to set email alerts
|

Wmap5 Observational Constraints on Braneworld New Inflation Model

Abstract: We study a new inflation potential in the framework of the Randall-Sundrum type 2 Braneworld model. Using the technic developped in[1], we consider both an monomial and a new inflation potentials and apply the Slow-Roll approximation in high energy limit, to derive analytical expression of relevant perturabtion spectrum. We show that for some values of the parameter n of the potential) we obtain an perturbation spectrum wich present a good agreement with recent WMAP5 observations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In Ref. [9], we have studied a more genaralized version of this potential in Branewold model, and shown that the observation bound are satisfied. On the other hand, Liddle et al [11] have shown that observational constraints can be respected for an monomial potential, in particular for n = 2.…”
Section: Monomial Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…In Ref. [9], we have studied a more genaralized version of this potential in Branewold model, and shown that the observation bound are satisfied. On the other hand, Liddle et al [11] have shown that observational constraints can be respected for an monomial potential, in particular for n = 2.…”
Section: Monomial Modelmentioning
confidence: 95%
“…Braneworld inflation, was mainly shown to play a fondamental role in divers cosmological investigations of early universe and has been proposed to solve some problems of actual cosmological observations like as dark energy [5], tachyonic inflation [6] or black holes systems [7,8]. Recently, some generalized potentials and supersymmetic versions were studied in the framework of Randall-Syndrum model and a best fit to recent observations was given [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The Randall-Sundrum Braneworldmodel was mainly studied and shown to give a very good agreement with recent observations [20,21]. In this cosmological scenario, the metric projected onto the brane is a spatially fat Friedmann-Robertson-Walker with scale factor a(t) and the Friedmann equation on the brane has the generalized form [22]…”
Section: Rs-ii Braneworld Modelmentioning
confidence: 73%
“…Braneworld inflation has become recently, a central paradigm describing early stage of the Universe. In this context, Randall-Sundrum model [6,7] has shown a great capacity to reproduce the experimental values of all inflationary perturbation spectrum [8]. So, it would be very interesting to study the cosmological implications of these supersymmetric hybrid inflationary theories in braneworld model.…”
Section: Introductionmentioning
confidence: 99%